Quiescent ultra-diffuse galaxies in the field originating from backsplash orbits - Benavides, José A.; Sales, Laura V.; Abadi, Mario G.; Pillepich, Annalisa; Nelson, Dylan; Marinacci, Federico; Cooper, Michael; Pakmor, Rüdiger; Torrey, Paul; Vogelsberger, Mark; Hernquist, Lars (Nature astronomy, 2021)
Ultra-diffuse galaxies (UDGs) are the lowest-surface-brightness galaxies known, with typical stellar masses of dwarf galaxies but sizes similar to those of larger galaxies such as the Milky Way1. The reason for their extended sizes is debated, with suggested internal processes such as angular momentum2, feedback3,4 or mergers5 versus external mechanisms6-9 or a combination of both10. Observationally, we know that UDGs are red and quiescent in groups and clusters11,12 whereas their counterparts in the field are blue and star-forming13-16. This dichotomy suggests environmental effects as the main culprits. However, this scenario is challenged by recent observations of isolated quiescent UDGs in the field17-19. Here we use the ΛCDM (or Λ cold dark matter, where Λ is the cosmological constant) cosmological hydrodynamical simulation to show that isolated quenched UDGs are formed as backsplash galaxies that were once satellites of another galactic, group or cluster halo but are today a few Mpc away from them. These interactions, albeit brief, remove the gas and tidally strip the outskirts of the dark matter haloes of the now quenched and seemingly isolated UDGs, which are born as star-forming field UDGs occupying dwarf-mass dark matter haloes. Quiescent UDGs may therefore be found in non-negligible numbers in filaments and voids, bearing the mark of past interactions as stripped outer haloes devoid of dark matter and gas compared to dwarfs with similar stellar content.